Augmented β-Cell Function and Mass in Glucocorticoid-Treated Rodents Are Associated with Increased Islet Ir-β/AKT/mTOR and Decreased AMPK/ACC and AS160 Signaling. (17th September 2014) - Protzek, André O. P.; Costa-Júnior, José M.; Rezende, Luiz F.; Santos, Gustavo J.; Araújo, Tiago Gomes; Vettorazzi, Jean F.; Ortis, Fernanda; Carneiro, Everardo M.; Rafacho, Alex; Boschero, Antonio C.
Abstract : Glucocorticoid (GC) therapies may adversely cause insulin resistance (IR) that lead to a compensatory hyperinsulinemia due to insulin hypersecretion. The increased β -cell function is associated with increased insulin signaling that has the protein kinase B (AKT) substrate with 160 kDa (AS160) as an important downstream AKT effector. In muscle, both insulin and AMP-activated protein kinase (AMPK) signaling phosphorylate and inactivate AS160, which favors the glucose transporter (GLUT)-4 translocation to plasma membrane. Whether AS160 phosphorylation is modulated in islets from GC-treated subjects is unknown. For this, two animal models, Swiss mice and Wistar rats, were treated with dexamethasone (DEX) (1 mg/kg body weight) for 5 consecutive days. DEX treatment induced IR, hyperinsulinemia, and dyslipidemia in both species, but glucose intolerance and hyperglycemia only in rats. DEX treatment caused increased insulin secretion in response to glucose and augmented β -cell mass in both species that were associated with increased islet content and increased phosphorylation of the AS160 protein. Protein AKT phosphorylation, but not AMPK phosphorylation, was found significantly enhanced in islets from DEX-treated animals. We conclude that the augmented β -cell function developed in response to the GC-induced IR involves inhibition of the islet AS160 protein activity.